2006
DOI: 10.1016/j.bbr.2006.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of delay aversion and response inhibition to extinction learning, aggression, and sexual behaviour

Abstract: Impulsivity is an important symptom of many psychiatric disorders, and can be divided into two subtypes: response inhibition deficits and delay aversion. In the present study, we investigated the relationship between delay aversion and response inhibition, both to each other and to locomotion, extinction of conditioned responses, sexual behaviour, and aggressive behaviour. To that end, we quantified the behaviour of 24 rats in several tests. To measure response inhibition, rats were trained in a stop-signal ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 61 publications
3
28
1
Order By: Relevance
“…Svensson et al (2000) also found that gonadectomy decreased impulsivity, and this effect was reversed in rats that received testosterone substitution after gonadectomy. Thus, two studies are in agreement that testosterone in males is related to higher levels of impulsivity; however, in a third study, there was no relationship between plasma testosterone and impulsivity in male rats (Van den Bergh et al 2006). Results from another study suggested that testosterone's effects may be baseline-dependent (Takahashi et al 2006); that is, testosterone enhanced impulsive choice in nonimpulsive men, and it decreased impulsive choice in impulsive men (Takahashi et al 2006).…”
Section: Sex and Hormonal Factorsmentioning
confidence: 78%
See 2 more Smart Citations
“…Svensson et al (2000) also found that gonadectomy decreased impulsivity, and this effect was reversed in rats that received testosterone substitution after gonadectomy. Thus, two studies are in agreement that testosterone in males is related to higher levels of impulsivity; however, in a third study, there was no relationship between plasma testosterone and impulsivity in male rats (Van den Bergh et al 2006). Results from another study suggested that testosterone's effects may be baseline-dependent (Takahashi et al 2006); that is, testosterone enhanced impulsive choice in nonimpulsive men, and it decreased impulsive choice in impulsive men (Takahashi et al 2006).…”
Section: Sex and Hormonal Factorsmentioning
confidence: 78%
“…Performance on laboratory measures of impulsive choice and inhibition are not necessarily related in humans (Dalen et al 2004;Solanto et al 2001;Sonuga-Barke 2003;Sonuga-Barke et al 2003) or rats (Van den Bergh et al 2006). There are most likely individual differences in the extent to which these two manifestations of impulsivity are present.…”
Section: Operational Measures Of Impulsivitymentioning
confidence: 95%
See 1 more Smart Citation
“…Indirect support for a lack of effect of serotonin in the mediation of action cancellation comes from a study by van den Bergh et al (2006) who found no link in rats between aggression towards intruders and slowing of SSRT, although they did find a direct correlation between this form of aggression and another form of behavioural disinhibition, impulsive choice (delayed gratification). This indirectly supports the lack of effect of serotonin in the control of stopping because there are links between serotonin and some, although not all, forms of aggression.…”
Section: Role Of 5-ht In Action Cancellationmentioning
confidence: 99%
“…Response inhibition models assess the subject"s ability to inhibit responding [20], [21], [22], and delayed reward models measure an animal"s choice between a small, immediate reinforcer, and a large, delayed reinforcer, assessing "impulsive choice", an index of impulsivity [23], [24]. Van den Bergh et al [25] investigated the relationship between response inhibition and delay aversion in rats, suggesting that response inhibition and delay aversion are independent measures of impulsivity, consistent with previous findings in humans [18].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%